Functional Gene Expression Differentiation of the Notch Signaling Pathway in Female Reproductive Tract Tissues—A Comprehensive Review With Analysis - Orzechowska, Magdalena; Anusewicz, Dorota; Bednarek, Andrzej K. (Frontiers in Cell and Developmental Biology, 2020)
The Notch pathway is evolutionarily conserved signaling regulating the development of the female tract organs such as breast, ovary, cervix, and uterine endometrium. A great number of studies revealed Notch aberrancies in association with their carcinogenesis and disease progression, which management is still challenging. The present study is a comprehensive review of the available literature on the Notch signaling during the normal development and carcinogenesis of the female tract organs. The review has been enriched with our analyses of the TCGA data including breast, cervical, ovarian, and endometrial carcinomas concerning the effects of Notch signaling at two levels: the core components and downstream effectors, hence filling the lacks in the global overview of Notch-driven carcinogenesis and disease progression. Phenotype heterogeneity regarding Notch signaling was projected in two Uniform Manifold Approximation and Projection algorithm dimensions, preceded with the Principal Component Analysis step reducing the data burden. Additionally, overall and disease-free survival analyses were performed with the optimal cutpoint determination by EvaluateCutpoints software to establish the character of particular Notch components in tumorigenesis. In addition to the review, we demonstrated separate models of the examined cancers of the Notch pathway and its targets, although expression profiles of all normal tissues were much more similar to each other than to its cancerous compartments. Such Notch-driven cancerous differentiation resulted in a case of opposite association with DFS and OS. In the consequence target genes show also very distinct profiles including genes associated with cell proliferation and differentiation, energy metabolism, or the EMT. Concluding, the observed Notch associations with the female tract malignancies resulted from differential expression of its target genes. This may direct a future analysis to search for new therapeutic targets based on specific Notch pathway profiles.